Assessing the cost‐effectiveness of a fluoride varnish programme in Chile: The use of a decision analytic model in dentistry. Issue 3 (19th February 2019) - Palacio, Raul; Shen, Jing; Vale, Luke; Vernazza, Christopher Robert
Abstract: Objectives: This study illustrates the use of a decision analytic model (DAM) to evaluate whether fluoride varnish application (FV) increases the proportion of caries‐free children in the Chilean preschool population, at an acceptable cost. Methods: Different FV interventions were compared with an oral health counselling‐only intervention. The FV interventions were tested (with and without screening) every 6 months over 2 years, in either a preschool setting or during a well‐child programme appointment in a primary care setting. A Markov model was developed to simulate the FV performance. The model was populated with data obtained from Chilean epidemiologic studies, a systematic review and a costing study. The counselling‐only intervention was compared with FV interventions to estimate the incremental cost per child. As there was uncertainty in terms of precise parameter values both probabilistic and deterministic sensitivity analyses were performed. Results: Delivery of FV in a primary care setting without screening was the most effective and the least costly intervention. Compared with counselling‐only intervention, this intervention increased the prevalence of caries‐free children in the population by 3.7%, with an extra cost (in March 2015) of £3 per caries‐free child. The results were sensitive to the starting age of FV application; increasing age would reduce the cost‐effectiveness of the FV intervention. Furthermore, cost‐effectiveness improves if some equipment such as an oral hygiene kit was not used and if less costly but qualified staff applied FV rather than dentists. Conclusions: This analysis allowed the comparison of the performance of FV in realistic scenarios incorporating important aspects of health and education policies. The application of FV in a primary care setting was the most cost‐effective strategy. The work demonstrated that both the methodology and results are useful for decision‐makers.